2021
DOI: 10.1111/1365-2664.13903
|View full text |Cite
|
Sign up to set email alerts
|

Modelling short‐term energetic costs of sonar disturbance to cetaceans using high‐resolution foraging data

Abstract: Abbreviations: A, Stroke amplitude (m); C L , Mass-specific locomotor cost of a stroke (kJ stroke −1 kg −1 ); E, Energy cost of disturbance (kJ); E*, Relative energetic cost of disturbance (unitless); E p , Energy acquired per prey capture event (kJ/event); f, Stroke frequency (Hz); Δf, Change in stroke frequency (Hz); P a , Rate of energy acquisition (kJ/hr); ΔP e , Change in rate of energy expenditure (kJ/hr); PCoD, Population Consequences of Disturbance; r f , Feeding rate (event/hr); St, Strouhal number (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 133 publications
0
19
2
Order By: Relevance
“…A key assumption, however, is that responses are comparable and detection rates equal between tag types. This is an important caveat, as the energetic costs associated with sonar disturbance vary with the nature and strength of behavioral responses, and are a function of species' life histories and physiologies (Czapanskiy et al, 2021). For example, the relative energy expenditure of a blue whale exhibiting a "mild" foraging response has been shown to exceed that of an "extreme" flight response in Cuvier's beaked whales (Czapanskiy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key assumption, however, is that responses are comparable and detection rates equal between tag types. This is an important caveat, as the energetic costs associated with sonar disturbance vary with the nature and strength of behavioral responses, and are a function of species' life histories and physiologies (Czapanskiy et al, 2021). For example, the relative energy expenditure of a blue whale exhibiting a "mild" foraging response has been shown to exceed that of an "extreme" flight response in Cuvier's beaked whales (Czapanskiy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important caveat, as the energetic costs associated with sonar disturbance vary with the nature and strength of behavioral responses, and are a function of species' life histories and physiologies (Czapanskiy et al, 2021). For example, the relative energy expenditure of a blue whale exhibiting a "mild" foraging response has been shown to exceed that of an "extreme" flight response in Cuvier's beaked whales (Czapanskiy et al, 2021). Failure to detect weak responses, or responses of a particular type, on instruments that deliver coarser-resolution data like S-TAGs would lead to bias in estimates of the dose-response functions and thus assessments of biological impacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, high-resolution archival tags are designed to provide detailed dive data over a short period of time (≤24 hrs) and therefore yield an incomplete picture of daily feeding activities that preclude assessing seasonal shifts in foraging effort. Consequently, estimates of annual and even daily foraging effort must be extrapolated beyond the available data (e.g., Savoca et al, 2021). This contrasts with what long-term satellite telemetry and time-depth recorder data have revealed for both the eastern (Laidre and Heide-Jorgensen, 2012;Nielsen et al, 2015;Chambault et al, 2018;Fortune et al, 2020c) and western (Citta et al, 2015;Olnes et al, 2020;Citta et al, 2021) bowhead whale populations.…”
Section: Seasonality In Foraging Behaviour and Fastingmentioning
confidence: 95%
“…This was then multiplied by the response duration ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\zeta $\end{document} ), which here was assumed to be equal to disturbance source duration, to give daily response cost ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\upsilon$\end{document} ; Table 2 , row 51). Energetic costs of increased locomotion during response are thought to be low compared with those of lost feeding opportunities, unless the change in locomotion is dramatic ( Czapanskiy et al , 2021 ). Isojunno et al (2020b ) found no strong support for a change in activity level during response, so field metabolic rate ( κ ; Table 2 , row 46) was assumed to be unchanged during response.…”
Section: Methodsmentioning
confidence: 99%